Prevalence rates of childhood abuse experiences among a sample of Saudi adolescents in light of some demographic variables - Elsayed, Fatima Khalifa; Muashi, Layla Mohammad; Almoaither, May Saad (Journal of Educational and Psychological Sciences, 2022)
Abuse experiences in childhood are the most prevalent phenomena in societies, and the most severe and dangerous bad experiences, as they have a very important direct and indirect impact on the psychological and social health of individuals and their future career.This research aimed to investigate the prevalence of childhood abuse among a sample of Saudi adolescents, and to discover whether or not there are differences in the average scores of childhood abuse attributed to the variables of gender or economic level of the family. The study included a sample of (233) adolescents whose ages ranged from 12 to 20 years-old. The sample was collected randomly, and the researchers utilized Childhood Abuse Experience Scale, found by (Fatima Khalifa Al-Sayed, 2015). Results revealed that there was average level of experience of childhood abuse in the sample, and the results also found that there were no statistically significant differences between the averages of the grades of the experience of abuse in childhood, while the results found statistically significant differences between average scale scores for low economic levels. The researchers made a set of recommendations, such as training school psychologists and social workers on how to deal with the category of students subjected to (emotional / sexual) abuse and providing them with treatment plans, as well as raising the awareness of parents about the need to protect their children from various types of abuse.